Cuerpo, Género y Poder en la escuela: el caso de la Educación Física Escolar Argentina (1880-1930) - Scharagrodsky, Pablo Ariel (2001)
The article makes an exhaustive social-historical revision of the physical education at schools in Argentina, and its implications in relation to masculine -and feminine- bodies. This analysis identifies two greater marks, which have oriented the corporal practices in the period between 1880-1930: on one hand, the military sign, and, on the other, the hygienic sign. Both marks have had a strong prescriptive impact, which has shown, in a special way, the contribution to the construction of certain masculinity.
O artigo realiza uma exaustiva revisão histórico-social da educação física escolar argentina e de suas implicaçoes em relação ao corpo masculino - e feminino. A análise identifica duas grandes características que condicionaram as práticas esportivas durante o período de 1880 a 1930: por um lado o aspecto militar, por outro o higiénico. Essas práticas tiveram um forte impacto prescritivo, que colocou cm relevo, de forma muito especial, a contribuição para a construção de uma certa masculinidade.